2016
DOI: 10.1177/1468087416640439
|View full text |Cite
|
Sign up to set email alerts
|

Influences of intake ports and pent-roof structures on the flow characteristics of a poppet-valved two-stroke gasoline engine

Abstract: In order to minimize the short-circuiting of the intake charge in a poppet-valved two-stroke engine, a ''step structure'' on the intake side of the pent-roof was employed to shroud the bulk flow at the upper periphery of the intake valves at low valve lifts. Several intake-port geometries and pent-roof angles were evaluated on their charging and reversed tumble generating abilities using a steady flow test rig built in computational fluid dynamics, among which top-entry ports and relatively small pent-roof ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The experimental jockey structure in Figure 2c results to α ≈ 120 • . As is schematically shown in Figure 2e and closely related to the vertical intake port design [11], fresh gas then descends down to the piston (in this phase near BDC) and U-turns toward the outlet region (loop scavenging), thereby more effectively replacing the cylinder's volume before entering the outlet. The directional nozzle, formed by the valve disk and jockey and effective in the last possible placement of the flow, can enforce a comparably intense tumbling, as shown below.…”
Section: A Presumably Forgotten Solutionmentioning
confidence: 99%
See 3 more Smart Citations
“…The experimental jockey structure in Figure 2c results to α ≈ 120 • . As is schematically shown in Figure 2e and closely related to the vertical intake port design [11], fresh gas then descends down to the piston (in this phase near BDC) and U-turns toward the outlet region (loop scavenging), thereby more effectively replacing the cylinder's volume before entering the outlet. The directional nozzle, formed by the valve disk and jockey and effective in the last possible placement of the flow, can enforce a comparably intense tumbling, as shown below.…”
Section: A Presumably Forgotten Solutionmentioning
confidence: 99%
“…A potentially attractive concept for a qualitatively advantageous 2-stroke scavenging in an almost normal 4-stroke design is presented via a modified intake valve ( Figure 2) which, by itself, induces a directed flow instead of changing the complete cylinder head and intake geometry [8][9][10][11] or the combustion chamber [12,13]. It must be noted that a modified inlet valve for 2-stroke operation is not a new idea but was already treated by many and mostly outdated patent applications, including a very related invention from Jeong et al [17] in 1996.…”
Section: A Presumably Forgotten Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mattarelli et al reported a CFD study on a two-stroke Opposed Piston High Speed Direct Injection Diesel Engine (OPHSDI) and analyzed the influence of the offset between the crankshafts by performing 3D CFD simulations [20]. Li et al investigated the influences of intake ports and pent-roof structures on the flow characteristics of a poppet-valved two-stroke gasoline engine to minimize the short-circuiting of the intake charge [21]. He et al emphasized the significant effects of exhaust back pressure, porting timing, and intake port layout on the scavenging quality and trapped air mass in cylinder by transient CFD simulation, including blow-down and scavenging [22].…”
Section: Introductionmentioning
confidence: 99%